Socio-Anthropological Analysis of Vulnerability Assessment and Polycentric Disaster Governance - Satyal, Kedar (Prashasan: The Nepalese Journal of Public Administration, 2024)
Vulnerability signifies deficiencies resulting from hazardous events that affect individuals, organizations, and networks within society. Assessing vulnerability aims to raise awareness among individuals in society and is estimated through indicators/indices, mostly pertaining to sociology and anthropology. Various socio-anthropological and scientific models/frameworks are utilized to assess and estimate disaster vulnerability during hazardous times. Polycentric disaster governance (PDG) can be more effective through adaptability, accountability, multiplicity (of organizations), etc., along with co-planning, co-designing, and co-implementing policies and provisions to minimize property destruction and loss of life caused by disasters, utilizing vulnerability data. Nepal's complex topographic structure and diverse practices contribute to higher vulnerability to disasters. Through PDG, both de-jure independence (decision-making) and de-facto autonomy support the achievement of SDGs targets and prosperity. In Nepal, three tiers of government and other entities are involved in co-planning and co-implementing disaster governance strategies.